Mathematics. (Chicago : World Book, 2009)
"An exploration of the transformative impact of inventions and discoveries in mathematics. Features include fact boxes, sidebars, biographies, timeline, glossary, list of recommended reading and Web sites, and index"--Provided by publisher.
Abacus -- Numerals -- Fractions -- Units of length -- Pythagorean theorem -- Geometry -- Prime numbers -- Value of Pi -- Algebra -- Concept of zero -- Decimal system -- Sector -- Calculators -- Probability theory -- Binary number system -- Calculus -- Metric system -- Mechanical computer -- Chaos theory -- Important dates in mathematics.
Includes bibliographical references and index.
Keywords: MATHEMATICS -- STUDY AND TEACHING (SECONDARY) -- JUVENILE LITERATURE